Navigating copyright: strategies for managing orphan works in cultural and memory institutions in Malaysia / Muhamad Helmi Muhamad Khair, Farizah Mohamed Isa and Haswira Nor Mohamad Hashim - Muhamad Khair, Muhamad Helmi; Mohamed Isa, Farizah; Mohamad Hashim, Haswira Nor (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
"Orphan works" are works (such as essays, songs, photographs, paintings, and sculptures) that are still copyrighted but cannot be contacted or identified by prospective users. While permission to use is essential in copyright law, it cannot be obtained, particularly in the context of "orphan works". Several international organisations have attempted to estimate the size of orphan works. In the United Kingdom, for example, the Collections Trust and Strategic Content Alliances surveyed 500 institutions and estimated that their collection contains approximately 13 million orphan works. Malaysia is not immune to the situation. According to preliminary findings from interviews with major cultural and memory institutions in Malaysia, orphan works are likely to make up between 1 and 20% of their collections, indicating the potential legal risks in collection management, necessitating an effective and secure management strategy. This situation is exacerbated further by the lack of existing policies and legal loopholes in Malaysia regarding orphan works. On this basis, this paper sought to address the following two research questions: (i) What are the current strategies for providing access to orphan works? and (ii) "What strategies can cultural and heritage institutions in Malaysia implement? Through doctrinal analysis and library-based research, this paper discovered that Malaysia's existing laws are insufficient to assist cultural and heritage institutions in the management of orphan works in their institutions. Following that, this paper included several strategic recommendations, such as thorough search procedures and accurate record maintenance for items placed in the aforementioned institutions.